2020
DOI: 10.1371/journal.pone.0228828
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient antibiofilm and antifungal activity of green propolis against Candida species in dentistry materials

Abstract: This study evaluated the effect of green propolis extract on the adhesion and biofilm formation of Candida species in dentistry materials. Phytochemical analysis of green propolis extract was performed by high-performance liquid chromatography. Adhesion was quantified by counting the number of yeast cells adherent to dental material fragments in a Neubauer chamber. Biofilm formation was determined by counting colony-forming units recovered from dental material fragments. The intensity of biofilm adhesion was c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
2
11
0
1
Order By: Relevance
“…However, Tobaldini-Valerio and collaborators [72] observed that green propolis effectively affected the biofilm formation by C. albicans, C. parapsilosis and C. tropicalis, but in a species-and strain-dependent manner. In another study, similar results were obtained for green propolis, and the biofilm Sokolonski et al BMC Complementary Medicine and Therapies (2021) 21:286 formation by C. albicans was significantly more reduced when compared to C. parapsilosis and C. tropicalis [73]. In our work, the majority of the RP_EtOH concentrations tested were able to reduce biofilm formation (more than 80%) in the three species tested herein.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, Tobaldini-Valerio and collaborators [72] observed that green propolis effectively affected the biofilm formation by C. albicans, C. parapsilosis and C. tropicalis, but in a species-and strain-dependent manner. In another study, similar results were obtained for green propolis, and the biofilm Sokolonski et al BMC Complementary Medicine and Therapies (2021) 21:286 formation by C. albicans was significantly more reduced when compared to C. parapsilosis and C. tropicalis [73]. In our work, the majority of the RP_EtOH concentrations tested were able to reduce biofilm formation (more than 80%) in the three species tested herein.…”
Section: Discussionsupporting
confidence: 88%
“…In our work, the majority of the RP_EtOH concentrations tested were able to reduce biofilm formation (more than 80%) in the three species tested herein. Most studies had tested the ability of propolis to act on the already formed biofilm [73][74][75], but as the CDC advises [76], the best way to fight resistant infections is through prevention. Thus, propolis can be used to prevent colonization on abiotic surfaces and in infections by resistant Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that the number of studies on the evaluation of the effects of propolis in vulvovaginal candidiasis (opportunistic fungal infection) is increasing [25,27,71,72]. New trends in antifungal research of propolis include also assessment of anti-candidal activities i.e., in orthodontic materials (green propolis) [73], dental surface (red propolis) [61,74], in treatment of chronic periodontitis (red propolis) [75], in caries (Brazilian and European propolis) [53]. The third research area is endemic and rare diseases.…”
Section: Antifungal Properties Of Propolismentioning
confidence: 99%
“…It is known that the antibacterial activity of propolis may vary depending on seasonality because the presence and concentration of its markers are related with the season, which in turn influences the production of secondary metabolites by the botanical origin of propolis (Regueiro et al, 2017;do Nascimento et al, 2019). The use of propolis on technological development in dentistry and oral health has been frequent because it is a nontoxic raw material, with traditional use in natural medicine and that shows some known pharmacological activities as antimicrobial, antiinflammatory and wound healing (Koo et al, 2002;Freires et al, 2016;Oliveirados et al, 2017;de Carvalho Furtado et al, 2018;Bezerra et al, 2020;da silva Barboza et al, 2021). It has been reported in scientific literature the use of propolis on development of varnish (De Luca et al, 2014;Neto et al, 2020), toothpaste (Wiatrak et al, 2017;Peycheva et al, 2019), total-etching adhesive system (Porto et al, 2021), cavity cleaning agent (Celerino de Moraes Porto et al, 2018) and endodontic irrigant (Parolia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Propolis has been used in dentistry and oral healthcare due to its pharmacological properties and absence of toxicity ensured even by its use in traditional medicine ( Sforcin and Bankova, 2011 ; da silva Barboza et al, 2021 ; Zulhendri et al, 2021 ). Among the possibilities of propolis use in dentistry and oral healthcare are: in inhibition of adhesion and biofilm formation of Candida species in dentistry materials ( Bezerra et al, 2020 ), on development of endodontic irrigants ( Parolia et al, 2021 ), on development of varnishes ( De Luca et al, 2014 ), on development of total-etching adhesive system ( Porto et al, 2021 ), as cavity cleaning agent ( Celerino de Moraes Porto et al, 2018 ), on mouthwash development ( Santiago et al, 2018 ), on gel formulation development ( González-Serrano et al, 2021 ) and on oromuco-adhesive films development ( Arafa et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%